2015
DOI: 10.1111/gbb.12207
|View full text |Cite
|
Sign up to set email alerts
|

Methyl‐donor deficiency in adolescence affects memory and epigenetic status in the mouse hippocampus

Abstract: DNA methylation is one of the essential factors in the control of gene expression. Alteration of the DNA methylation pattern has been linked to various neurological, behavioral and neurocognitive dysfunctions. Recent studies have pointed out the importance of epigenetics in brain development and functions including learning and memory. Nutrients related to one-carbon metabolism are known to play important roles in the maintenance of genomic DNA methylation. Previous studies have shown that the long-term admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 57 publications
(70 reference statements)
1
33
0
Order By: Relevance
“…Additionally, neuroprotective effects may be mediated through choline’s role as a methyl-donor [57]. Therefore, our findings that choline and choline-derived methyl-donor metabolites, such as betaine and SAM, are decreased in E− brains (Figure 9B) suggests disruption of methylation reactions that could subsequently affect cognition, since methyl-donor deficiency has been found to compromise learning by disturbing DNA and/or histone methylation in the brain [58]. …”
Section: Discussionmentioning
confidence: 98%
“…Additionally, neuroprotective effects may be mediated through choline’s role as a methyl-donor [57]. Therefore, our findings that choline and choline-derived methyl-donor metabolites, such as betaine and SAM, are decreased in E− brains (Figure 9B) suggests disruption of methylation reactions that could subsequently affect cognition, since methyl-donor deficiency has been found to compromise learning by disturbing DNA and/or histone methylation in the brain [58]. …”
Section: Discussionmentioning
confidence: 98%
“…DNMTs transfer methyl groups from S-adenosylmethionine (SAM) to cytosine [86], so diets lacking folate or other methyl donors can impede SAM synthesis, thereby leading to DNA hypomethylation [8789]. Depleting dietary methyl donor content has been shown to decrease DNA methylation markers in the brain [89], and impair fear memory [62, 90]. On the other hand, boosting levels of methyl donors (or SAM itself) increases DNA methylation levels in brain [91], and elicits antidepressant effects in rats and mice, such as decreased immobility in the FST and improved stress-induced anhedonia [9295].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies in mice found that chronic dietary methyl depletion interfered with contextual fear conditioning/memory, but did not impact anxiety-like behavior [62, 90, 102]. A study in Wistar rats combined methyl diet deficiency with chronic unpredictable stress and found that methyl donor deficiency improved chronic stress-elicited anxiety-like behavior, but did not affect FST immobility [103].…”
Section: Discussionmentioning
confidence: 99%
“…Lasting effects of reduced choline availability may partially underlie compromised cognition in the E− larvae, as demonstrated in mouse models of prenatal choline deficiency [44]. These consequences possibly are mediated by methyl donor-dependent epigenetic mechanisms [45] related to DNA methylation status, established either during the embryonic and/or larval periods.…”
Section: Discussionmentioning
confidence: 99%